EFFORTS TO INCREASE OPTIMAL COMMUNITY HEALTH THROUGH SCREENING OF NON-CONVENIENT DISEASES IN JOGONAYAN VILLAGE, MAGELANG REGENCY - Ainnur Rahmanti; Endro Haksara (Pusat Riset dan Inovasi Nasional, 2022)
Background Non-Communicable Disease Screening is a form of community participation in activities for early detection, monitoring and early follow-up of risk factors for non-communicable diseases independently and continuously. This activity was developed as a form of early awareness of non-communicable diseases considering that almost all risk factors for non-communicable diseases do not give symptoms to those who experience them. Risk factors for non-communicable diseases include smoking, consumption of alcoholic beverages, unhealthy eating patterns, lack of physical activity, obesity, stress, hypertension, hyperglycemia, hypercholesterolemia. Purpose is to improve the health status of the community through early detection of non-communicable diseases especially those with diabetes mellitus The method begins with interviews with health cadres in the Jogonayan village area, Magelang Regency, followed by an early detection program and health education. Results:. The health checks carried out were anthropometric measurements in the form of height, weight, abdominal circumference, blood pressure measurements and current blood sugar measurements. Of the 48 residents who took part in the detection, 37% had pre-hypertension, 15% had grade I hypertension and 18% had blood sugar >200 mg/dl and 10% did not suffer from hypertension or diabetes mellitus, 20% were in good health. Conclusion: Early detection of non-communicable diseases is very important to prevent further complications.